The effect of psychological empowerment on job burnout among executives in Petronas Penapisan (Melaka) Sdn Bhd / Ainul Farhana Husna Ismail and Nurul Anis Amylisa Jaafar - Ismail, Ainul Farhana Husna; Jaafar, Nurul Anis Amylisa (Faculty of Business and Management, 2015)
Nowadays burnout is commonly occur in our society. This support by Maslach & Jackson, (1981), Maslach, Schaufeli & Leiter, (2001) that state “burnout is a global problem happened in human service profession. Therefore, this research examined the effect of psychological empowerment on job burnout in a sample of executives in Petronas Penapisan (Melaka) Sdn. Bhd. The data collected through questionnaire from 115 respondents was used to test the proposed hypothesis. A self-administered, paper and pencil, mailed survey was used to collect data using three instruments: (a) Demographic data, (b) The Psychological Empowerment Scale and (c) The Maslach- Burnout Inventory-Emotional Exhaustion Subscale.